2013
DOI: 10.1007/s00401-013-1143-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-duration epilepsy affects cell morphology and glutamatergic synapses in type IIB focal cortical dysplasia

Abstract: To investigate hypothesized effects of severe epilepsy on malformed cortex, we analyzed surgical samples from eight patients with type IIB focal cortical dysplasia (FCD) in comparison with samples from nine non-dysplastic controls. We investigated, using stereological quantification methods, where appropriate, dysplastic neurons, neuronal density, balloon cells, glia, glutamatergic synaptic input, and the expression of N-methyl-D-aspartate (NMDA) receptor subunits and associated membrane-associated guanylate k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 52 publications
5
26
0
1
Order By: Relevance
“…Altogether this evidence suggests the progressive nature of severe seizures in both experimental models and humans [1][2]. In line with this hypothesis, we have very recently demonstrated that epilepsy duration was positively correlated with morphometric changes of both neurons and glia and greater glutamatergic input in the epileptogenic/dysplastic areas of FCD patients [86]. It is possible, therefore, that the progressive pathologic plasticity we describe here might also occur in severe, malformation-related human epilepsies.…”
Section: Discussionsupporting
confidence: 84%
“…Altogether this evidence suggests the progressive nature of severe seizures in both experimental models and humans [1][2]. In line with this hypothesis, we have very recently demonstrated that epilepsy duration was positively correlated with morphometric changes of both neurons and glia and greater glutamatergic input in the epileptogenic/dysplastic areas of FCD patients [86]. It is possible, therefore, that the progressive pathologic plasticity we describe here might also occur in severe, malformation-related human epilepsies.…”
Section: Discussionsupporting
confidence: 84%
“…7,[33][34][35] Alteration of the extracellular matrix through increased expression of metalloproteinase 9 leading to putative modified intra-and extracellular chloride levels has been reported. Previous studies reported several possible mechanisms underlying the epileptogenicity in FCD.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamatergic transmission supports ictogenesis in human FCD slices, 32 due to an increased expression and altered composition of NMDA (NR2B subunit) receptors. 7,[33][34][35] Alteration of the extracellular matrix through increased expression of metalloproteinase 9 leading to putative modified intra-and extracellular chloride levels has been reported. 36 Involvement of purinergic transmission was also proposed, via an excess of adenosine triphosphate release through pannexin 1 channels, 37 although this pathway is not specific to FCD epileptogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We found extensive reactive gliosis (with altered astrocyte morphology) in localized irritative region which corroborates finding that longer chronic epilepsy is associated with more intensive reactive gliosis and astrocyte alterations in epileptogenic region, further evidence that epilepsy is a progressive pathology (Finardi A, et al, 2013). Astrocytes undergo changes in morphology, molecular composition, and proliferation in epileptogenic region.…”
Section: Inflammatory Biomarkerssupporting
confidence: 89%